PELAKSANAAN PEMENUHAN KEWAJIBAN PAJAK PENGHASILANPASAL 23 ATAS JASA MAKLON PADA PT. PRIMA JIREH TAHUN 2015 DI JAKARTA - Ade Suryana; Devi Purnama Sari; Desy Nur Fadhilah (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2015)
Article 23 Income Tax is a tax deducted from income received or obtained by a Domestic Taxpayer (individual and entity) and Permanent Establishment (BUT) originating from capital, delivery of services or other activities other than those deducted by PPh 21. Purpose from this research is to find out whether the implementation of the Income Tax Article 23 deduction, deposit and reporting on PT Prima Jireh is in accordance with the applicable laws and regulations. One effort in collecting data on this final project is by conducting observations where the author conducts an internship. From the research conducted, it can be concluded that the implementation of Article 23 Income Tax deductions and deposits made by the company is not in accordance with the applicable laws and regulations because there are still Article 23 Income Taxes that have been late deposited and reported.